Efficacy and Safety of Hepatic Artery Infusion Chemotherapy Combined with Donafenib and Camrelizumab in the Treatment of Patients with Unresectable Hepatocellular Carcinoma: A Retrospective, Single-Arm Study - Wu C; Fu Z; Pan L; Li J; Zhou Y; Sun R; Gou Y; Zhao Y; Wang Z; Qiu Y; Huang P (Journal of Hepatocellular Carcinoma)
Chenrui Wu,1,* Zixuan Fu,1,* Long Pan,1 Jiachu Li,2 Yin Zhou,3 Ruirui Sun,1 Yang Gou,1 Yaowu Zhao,1 Zhouyan Wang,1 Yuhao Qiu,1 Ping Huang1 1Department of Hepatobiliary Surgery, First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 2Department of Oncology, First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 3Department of Radiology, First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ping Huang, Department of Hepatobiliary Surgery, The First Affiliated Hospital of Chongqing Medical University, No. 1, Youyi Road, Yuzhong District, Chongqing, 400016, People’s Republic of China, Email huangping4069@163.comPurpose: To evaluate the efficacy and safety of hepatic artery infusion chemotherapy with oxaliplatin, fluorouracil, and leucovorin (FOLFOX-HAIC) combined with donafenib and camrelizumab in patients with unresectable hepatocellular carcinoma (uHCC).Patients and Methods: This retrospective study analyzed clinical data from 49 uHCC patients treated with FOLFOX-HAIC, donafenib tablets, and camrelizumab at the First Affiliated Hospital of Chongqing Medical University between November 1, 2021, and November 30, 2024. The primary endpoint was the objective response rate (ORR), assessed according to Response Evaluation Criteria in Solid Tumors (RECIST) version 1.1 and modified RECIST (mRECIST). Secondary endpoints included surgical conversion rate, disease control rate (DCR), progression-free survival (PFS), overall survival (OS), duration of response (DOR), and safety.Results: The median follow-up duration was 20.3 months. Patients had a mean age of 55.9 years and a mean tumor diameter of 9.9 cm, with 25 patients (51%) presenting with extrahepatic metastasis. According to RECIST v1.1, the ORR was 57.1%, and the DCR was 79.6%. Under mRECIST criteria, the ORR increased to 59.2%, while the DCR remained at 79.6%. The median PFS was 12.1 months, and the median OS was 26.0 months. Twelve patients (24.5%) achieved successful conversion, with five patients (10.2%) undergoing surgery achieving R0 resections. Two patients (4.1%) achieved a pathological complete response (pCR). All patients experienced treatment-related adverse events (TRAEs), with Hypoalbuminemia (87.8%) and Hand-foot skin reaction (79.6%) being the most common. Grade 3 or higher TRAEs were observed in 61.2% of patients.Conclusion: For patients with uHCC, the combination therapy of FOLFOX-HAIC with donafenib and camrelizumab demonstrates favorable efficacy and manageable adverse events.Keywords: hepatocellular carcinoma, donafenib, camrelizumab, oxaliplatin, leucovorin, fluorouracil